The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.laa.2019.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Perfect quantum state transfer on the Johnson scheme

Abstract: For any graph X with the adjacency matrix A, the transition matrix of the continuous-time quantum walk at time t is given by the matrix-valued function H X (t) = e itA . We say that there is perfect state transfer in X from the vertex u to the vertex v at time τ if |H X (τ ) u,v | = 1. It is an important problem to determine whether perfect state transfers can happen on a given family of graphs. In this paper we characterize all the graphs in the Johnson scheme which have this property. Indeed, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…x ∈ G 0 } ≥ 2. On the other hand, (χ 6 (S), · · · , χ 9 (S)) = (−2, 2, 2, −2) and (d − χ 6 (S), · · · , d − χ 9 (S)) = (6,2,2,6). Thus for each y ∈ G 1 , v 2 (d − α y ) = v 2 (d − χ j (S)) = 1, j ∈ {6, 7, 8, 9}.…”
Section: A Characterization Of Abelian Cayley Graph Being Integralmentioning
confidence: 99%
“…x ∈ G 0 } ≥ 2. On the other hand, (χ 6 (S), · · · , χ 9 (S)) = (−2, 2, 2, −2) and (d − χ 6 (S), · · · , d − χ 9 (S)) = (6,2,2,6). Thus for each y ∈ G 1 , v 2 (d − α y ) = v 2 (d − χ j (S)) = 1, j ∈ {6, 7, 8, 9}.…”
Section: A Characterization Of Abelian Cayley Graph Being Integralmentioning
confidence: 99%
“…The phenomenon of perfect state transfer (PST) in quantum communication networks was originally introduced by Bose in [14]. This work has attracted much research interest since many applications have been found in quantum information processing and cryptography (see [1,2,3,5,11,15,17,18,34,38,37] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The dual-Hahn polynomials are attached to the Johnson scheme [17]. It should be noted however that while PST occurs in a spin chain based on the dual Hahn polynomials, no lifts are possible to unweighted graphs of the Johnson scheme [1,19] owing to parameter incompatibility. Moreover to our knowledge no analogue of the ordered Hamming scheme to which multivariate dual-Hahn would be connected has been designed.…”
Section: Discussionmentioning
confidence: 99%